THE EFFECT OF IMPROVER ADDITION ON SWEET BREAD MADE FROM WHEAT FLOUR - Subekah Nawa Kartikasari; Puspita Sari; Achmad Subagio (University of Sultan Ageng Tirtayasa, 2019)
Modified starch produced in the MOCAF manufacturing process is still not widely used, so further studies are needed regarding the utilization of modified MOCAF-based starch. According to Miyazaki et al., (2006), starch can be used to improve the quality of bread. The raw materials used in the research are ADIRA cassava and cakra flour for sweet bread. The method used RAL with 3 factors, A type of control treatment improver (without addition of improver), addition of improver (native) and improver (modification), treatment B with variations in the amount of treatment added water (480, 510, 540 ml), and treatment C with variations in the concentration of the number of improvers added (0.125, 5 and 1%), each was repeated 3 times. In the application of sweet bread the data obtained from the results of the study were analyzed using the ANOVA (Analysis of Variant) test, if the treatment had a significant effect (p <0.05), Duncan's Multiple Range Test would be carried out to see the differences in each treatment given. and continued the Effectiveness test to get the best treatment of bread produced. The lowest density value is 0.17 ± 0.00 (g / cm3) in the F3 improver (1% + 540 ml). The lowest texture was obtained after storage on day 1 of the F3 improver (1% + 540 ml) with a value of 36 ± 6 g / 10mm. Based on the sensory test, the overall breadth appearance score, the color of the inside of the bread, and the aroma, ranged from likes to the value of 4. The F3 improver treatment (1% + 540 ml) has a texture and taste which is preferred with values 4.25 and 4.25 and ease of swallowing with a value of 4.17. The effectiveness value of 0.8 in treatment F3 (1% + 540 ml). The conclusion is that the improver in F3 treatment is best used as an improver on sweet bread.